ANALYSIS OF FACTORS INFLUENCING THE PURCHASING DECISION OF FACIAL FOAM LABELED HALAL - Adinugraha, Hendri Hermawan; Nadhifah, Hesti Hanan (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2020)
Consumers in deciding the purchase are motivated by various factors. The purpose of this study is to analyze the effect of price, product quality, product design, and brand image on purchasing decisions. The type of data used is primary data, using e-questionnaires. The sampling technique uses purposive sampling. The analysis technique uses multiple regression. The analysis shows that the price has a positive and significant effect on purchasing decisions. Product quality has a positive and significant influence on purchasing decisions. Product design has a positive and significant effect on purchasing decisions. Brand image has a positive and significant influence on purchasing decisions. In the future, the company needs to set prices following the purchasing power of the people but still maintain product quality and pay attention to product design.